Efficiency of mitochondrially targeted gallic acid in reducing brain mitochondrial oxidative damage - Parihar, P.; Jat, D.; Ghafourifar, P.; Parihar, M. S. (Cellular and Molecular Biology, 2014)
Oxidative stress is associated with mitochondrial impairments. Supplying mitochondria with potent antioxidants can reduce oxidative stress-induced mitochondrial impairment. Gallic acid can be used to reduce oxidative burden in mitochondria. In order to increase the bioavailability of gallic acid inside the mitochondria we synthesized mitochondrially targeted gallic acid and explored its preventive effects against sodium nitroprusside induced oxidative stress in isolated mitochondria. Our observations revealed an increase in oxidative stress,decrease in reduced glutathione in mitochondria and increase in the mitochondrial permeability pore transition due to sodium nitroprusside treatment. Pre-treatment of gallic acid and mitochondrially targeted gallic acid to sodium nitroprusside treated mitochondria not only significantly reduced the oxidative stress but also prevented mitochondrial permeability pore transition to a significant difference. Mitochondrially targeted gallic acid was found more effective in reducing oxidative stress and mitochondrial permeability pore transition than gallic acid. We conclude that mitochondrially targeted gallic acid can be used for preventing mitochondrial impairment caused by oxidative stress.